A Model for Exploring Compatibility Between Applicants and Residency Programs: Right Resident, Right Program. Issue 1 (January 2021) - Winkel, Abigail Ford; Morgan, Helen Kang; Burk-Rafel, Jesse; Dalrymple, John L.; Chiang, Seine; Marzano, David; Major, Carol; Katz, Nadine T.; Ollendorff, Arthur T.; Hammoud, Maya M.
Abstract : Holistic review of residency applications is touted as the gold standard for selection, yet vast application numbers leave programs reliant on screening using filters such as United States Medical Licensing Examination scores that do not reliably predict resident performance and may threaten diversity. Applicants struggle to identify which programs to apply to, and devote attention to these processes throughout most of the fourth year, distracting from their clinical education. In this perspective, educators across the undergraduate and graduate medical education continuum propose new models for student-program compatibility based on design thinking sessions with stakeholders in obstetrics and gynecology education from a broad range of training environments. First, we describe a framework for applicant-program compatibility based on applicant priorities and program offerings, including clinical training, academic training, practice setting, residency culture, personal life, and professional goals. Second, a conceptual model for applicant screening based on metrics, experiences, attributes, and alignment with program priorities is presented that might facilitate holistic review. We call for design and validation of novel metrics, such as situational judgment tests for professionalism. Together, these steps could improve the transparency, efficiency and fidelity of the residency application process. The models presented can be adapted to the priorities and values of other specialties. Abstract : A conceptual framework for exploring compatibility between residency applicants and programs and enhanced screening is proposed to improve the application and selection process.